2012
DOI: 10.1186/1742-2094-9-168
|View full text |Cite
|
Sign up to set email alerts
|

Pre-infection physical exercise decreases mortality and stimulates neurogenesis in bacterial meningitis

Abstract: Physical exercise has been shown to increase neurogenesis, to decrease neuronal injury and to improve memory in animal models of stroke and head trauma. Therefore, we investigated the effect of voluntary wheel running on survival, neuronal damage and cell proliferation in a mouse model of pneumococcal meningitis. Mice were housed in cages equipped with voluntary running wheels or in standard cages before induction of bacterial meningitis by a subarachnoid injection of a Streptococcus pneumoniae type 3 strain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…pneumoniae reduced mortality and increased hippocampal neurogenesis as assessed by the density of doublecortin-, TUC (TOAD [Turned on after division])-4-and bromodeoxyuridine-plus neuronal nuclei-colabeled cells in the hippocampal dentate gyrus. This, however, did not result in an improvement of the Morris water maze performance testing hippocampal spatial learning and memory [210]. In an adult rat model of Str.…”
Section: Rehabilitationmentioning
confidence: 99%
“…pneumoniae reduced mortality and increased hippocampal neurogenesis as assessed by the density of doublecortin-, TUC (TOAD [Turned on after division])-4-and bromodeoxyuridine-plus neuronal nuclei-colabeled cells in the hippocampal dentate gyrus. This, however, did not result in an improvement of the Morris water maze performance testing hippocampal spatial learning and memory [210]. In an adult rat model of Str.…”
Section: Rehabilitationmentioning
confidence: 99%
“…For example, prior human and animal studies suggest associations between physical inactivity, immune function and susceptibility to upper respiratory infections. (Friman and Wesslen 2000; Walsh, Gleeson et al 2011; Araujo, Campos et al 2012; Gunzer, Konrad et al 2012; Liebetanz, Gerber et al 2012)(Matthews, Ockene et al 2002; Chubak, McTiernan et al 2006; Barrett, Hayney et al 2012) We have previously observed associations between chronic medical conditions and increased rates of sepsis, including many associated with lack of physical activity. (Wang, Shapiro et al 2012) Television watching has been associated with poor dietary habits, and obesity - a major consequence of poor diet and physical inactivity - is also independently associated with increased rates of sepsis.…”
Section: Introductionmentioning
confidence: 97%
“…In a second set of experiments with the same infection regime, male CRAMP-KO and -WT mice were infected and sacrificed 36 h after induction of meningitis without treatment with antibiotics and were either perfused with 4% formalin for immunohistochemical analysis or with 0.9% NaCl solution for RNA isolation. Bacterial titers were evaluated 36 h after infection in tissue homogenates of the cerebellum and spleen and in blood samples by plating 10-fold dilutions on blood agar plates and incubation for 24 h at 37°C with 5% CO 2 (detection limit 10 2 CFU/ml in tissue homogenates and 10 3 CFU/ml in blood samples) [20]. All animal experiments were approved by the Animal Care Committee of the University Hospital of Aachen and by the District Government in Recklinghausen, North Rhine-Westphalia, Germany.…”
Section: Methodsmentioning
confidence: 99%